1998
DOI: 10.1111/j.1365-2109.1998.tb01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Feed efficiency, nutrient retention and body composition of Nile tilapia, Oreochromis niloticus L., fed diets containing L-ascorbic acid, L-ascorbyl-2-sulphate or L-ascorbyl-2-polyphosphate

Abstract: Seven purified diets were formulated and fed to seven groups of Nile tilapia, Oreochromis niloticus L., fingerlings for 12 weeks. Six of the formulated diets contained 5 or 50 mg kg -1 of ascorbic acid equivalent supplied by either L-ascorbic acid (AA), L-ascorbyl-2-sulphate (AS) or L-ascorbyl-2polyphosphate (APP). The seventh basal diet was ascorbate-free and served as the control. The results of diet analysis for ascorbic acid showed that it was not detected or negligible in the control diet and in the diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
2
1
0
1
Order By: Relevance
“…In the treatment diets, the nitrogen recovery percentage was 40.6–45.8%, while ammonia excretion and faecal nitrogen were 45.4–47.7% and 8.0–11.6% respectively. These results compare well with the range of nitrogen retention (30–58%) in Nile tilapia fed balanced diets (Abdelghany 1998) with 35% protein in the dry matter and variable amounts of ascorbic acid from different sources. The range of ammonia excretion in this trial compares with the reported range (41–48%) for fish receiving diets with 15% and 45% vegetable protein (Gomes et al 1993) as well as the nitrogen recovery (43–49%) in sea bass ( Lates calcarifer ) reported by Chaimongkol & Boonyaratpalin (2001).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the treatment diets, the nitrogen recovery percentage was 40.6–45.8%, while ammonia excretion and faecal nitrogen were 45.4–47.7% and 8.0–11.6% respectively. These results compare well with the range of nitrogen retention (30–58%) in Nile tilapia fed balanced diets (Abdelghany 1998) with 35% protein in the dry matter and variable amounts of ascorbic acid from different sources. The range of ammonia excretion in this trial compares with the reported range (41–48%) for fish receiving diets with 15% and 45% vegetable protein (Gomes et al 1993) as well as the nitrogen recovery (43–49%) in sea bass ( Lates calcarifer ) reported by Chaimongkol & Boonyaratpalin (2001).…”
Section: Discussionsupporting
confidence: 80%
“…The low lipid content of tilapia fed duckweed-supplemented diets could be explained by three reasons. Vitamin C, which may be present in appreciable amounts in duckweed, induces lipolysis and decreases tissue lipid in tilapia by increasing its dietary concentration (Abdelghany 1998). The higher lipid content of the control diet may be a reason that tilapia fed on control diet had a higher lipid content, since Giri, Sahoo, Sahu & Mukhapadhyay (2000) reported that the body lipid content increases with the dietary lipid increment.…”
Section: Faeces Recovery and Nitrogen Mass Balancementioning
confidence: 99%
“…Oreochromis niloticus exposed to chronic concentration of M. oleifera revealed a decrease in body weight gain compared to control group (Table 5), this could be due to reduction in food consumption and/or decrease in gross food conversion rate. Inhibition of growth was also reported by Abdelghany (1998).…”
Section: Discussionsupporting
confidence: 55%
“…A utilização de formas protegidas, como o ácido ascórbico revestido com polímero sintético, glicerídeo ou etilcelulose (Shelbaek et ai., 1990) e, principalmente, de formas mais estáveis como ascorbato-2-monofosfato ou ascorbato-2-polifosfato, teria sido uma alternativa para conservar os níveis de vitamina C mais próximos do nível desejado (EI Naggar & Lovell 1991a;Mustin & Lovell, 1992;Gadient & Schai, 1994;Gadient & Fenster, 1994;Phromkunthong et ai., 1994;Woodward, 1994, Abdelghany, 1998e Kubitza et ai., 1998 Uma hipótese que poderia explicar a igualdade entre os tratamentos seria a quantidade de vitamina C contida em cada um dos ingredientes utilizados na formulação.…”
Section: Ensaiounclassified